Developing CB3AS Teaching Module to Improve Speaking Proficiency among EFL Business English Undergraduates at a Chinese Higher Education Institution: a Proposal - Ke Hu; Asmaa AlSaqqaf; Esther Jawing (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2022)
The technological revolution, globalization, and the increasing exposure to different cultural communication, English language teaching (ELT) have led to several reforms in the Chinese higher education system. Meanwhile, English for specific purposes (ESP) has also gained an extraordinary attention resulting in comprehensive developments of ELT in China. However, business English (BE), which is one of the disciplines of ESP, is considered challenging for Chinese EFL learners in higher education. Additionally, mastering a fluent English-speaking skill is extremely difficult for those learners compared with the other language skills (i.e., listening, reading, and writing). Accordingly, a growing need emerges for a curriculum development to improve the Chinese ESP learners’ speaking proficiency particularly in business-related areas. Therefore, this paper aims at bridging the gap between theory and practice by proposing a conceptual framework that integrates the approach of content-based instruction (CBI) and Thornbury’s 3As model (awareness, appropriation, and autonomy) into developing a localized teaching module to enhance the speaking proficiency among Chinese EFL learners of BE major in higher education. Adopting an explanatory mixed-method research design, this study will employ a quasi-experimental design with a purposive sampling where students from two classes of BE major from a private university in China will be involved in the study. A CB3As Speaking Teaching Module for a 14-week intervention will be implemented for the experimental group, while a traditional method will be used with the control group. Pre-test and post-test will be conducted to identify whether there is any significant difference in the mean score of the pre-test and post-test given to the two groups before and after the intervention. It is hoped that the results of this study would contribute to improving the speaking skill among Chinese EFL learners.